STRATEGI PENGEMBANGAN PEMASARAN DAN PEMBUKUAN PADA UMKM RISOL MAYO “CAK GENDUT” - Indra Puji Astuti; Andy Febri Alexander; Devi Citra Mayasari (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Competition for jobs is so tight that opening your own business is an alternative way of choosing a livelihood. Micro, Small and Medium Enterprises (MSMEs) are the most strategic social economic sector and concern the livelihoods of many people, making them the backbone of the national economy. However, the problems faced by the Risol Mayo